The Application of Hermeneutical Analysis to Research on the Cold War in Soviet Animation Media Texts from the Second Half of the 1940s. Issue 3 (3rd May 2016) - Fedorov, A.V.
Abstract : The Cold War era, which spawned a mutual ideological confrontation between communist and capitalist countries, left its mark on all categories of media texts, including cartoons and animations. Cartoons were used by the authorities as tools for delivering the necessary confrontational ideological content in an attractive folkloric, fairy-tale packaging in order to influence adults as well as children.